Extraordinary Wealth, Globalization, and Corruption - Benno Torgler; Marco Piatti (Center for Research in Economics, Management and the Arts (CREMA), 2009)
The billionaires of the world attract significant attention from the media and the public. The popular press is full of books selling formulas on how to become rich. Surprisingly, only a limited number of studies have explored empirically the determinants of extraordinary wealth. Using a large data set we explore whether globalization and corruption affect extreme wealth accumulation. We find evidence that an increase in globalization increases super-richness. In addition, we also find that an increase in corruption leads to an increase in the creation of super fortune. This supports the argument that in kleptocracies large sums are transferred into the hands of a small group of individuals.
Keywords: 330; Globalization; Extraordinary Wealth; Corruption; Superstars